1302Potential exposure-response relationships between vitamin D and cognitive performance in middle to older-aged adults. (2nd September 2021) - Harse, Janis; Zhu, Kun; Bucks, Romola; Hunter, Michael; Lim, Ee Mun; Cooke, Brian; Walsh, John; Murray, Kevin
Abstract: Background: Low vitamin D status is consistently associated with poorer global cognition in older adults, particularly women, but findings in relation to higher status are unclear. A better understanding of the relationship across the range is required. Methods: We investigated patterns of association between serum levels of 25-hydroxyvitamin D (25OHD), the standard measure of vitamin D status, and cognitive performance in 4872 middle to older-aged adults from the Busselton Healthy Ageing Study. Global cognition and performance in domains of attention, memory, and executive function were modelled using linear regression and restricted cubic splines, while controlling for demographic, lifestyle, and health factors. Results: Mean (SD) serum 25OHD levels were 78 (24) nM/L for women and 87 (25) nM/L for men. Positive, linear patterns for global cognition in women (p = 0.023) and attention accuracy in men (p = 0.022) suggested cognitive performance improved throughout the range. A non-linear pattern for attention accuracy in women suggested performance improved up to 25OHD levels of approximately 80 nM/L and then plateaued (p = 0.035). In men, negative patterns for semantic verbal fluency (linear, p = 0.025) and global cognition (non-linear, p = 0.015) suggested performance declined as 25OHD levels increased. Conclusions: Effects were small and patterns of association were inconsistent for men and women and across domains. However, the positive patterns identified for women, particularly in relation to attention accuracy, have biological plausibility as early, exposure-response relationships.